Pengaruh story telling menggunakan funny hand puppet tentang mitigasi bencana banjir terhadap tingkat pengetahuan siswa sekolah dasar - Tirtayanti, Sri; Sari, Rosi Solikah; Zandra, Ade (Holistik Jurnal Kesehatan, 2025)
Background: Indonesia, as a disaster-prone country, requires a relevant mitigation education approach for children, especially elementary school students. Children require learning media that not only provides information but also captures their attention. Funny hand puppets, as visual and verbal aids, can be an innovative solution for delivering disaster mitigation material. Early disaster mitigation education is a strategic step to build awareness and preparedness for potential disasters. For elementary school students, interactive and enjoyable delivery methods are needed to facilitate understanding. One effective method is storytelling using funny hand puppets. Purpose: To determine the effect of storytelling using funny hand puppets about flood mitigation on elementary school students' knowledge levels. Method: A quantitative pre-post-test one-group study was conducted in May 2025 at Bina Insan Islamic Elementary School, Palembang. The sampling technique used total sampling with a sample size of 30 participants. The independent variable in this study was the storytelling of funny hand puppets, while the dependent variable was knowledge level. Data analysis used univariate analysis in the form of frequency distributions and bivariate analysis using the Wilcoxon test. Results: There was a significant increase in students' knowledge levels after the storytelling intervention using funny hand puppets. The median knowledge score increased from 9.73 to 11.40 with a p-value of 0.000 (p < 0.05). Conclusion: There was a significant effect before and after the intervention on flood disaster mitigation on students' knowledge levels.   Keywords: Educated; Hand Puppet; Knowledge; Mitigation; Story Telling Funny.   Pendahuluan: Indonesia sebagai negara rawan bencana membutuhkan pendekatan edukasi mitigasi yang relevan untuk anak-anak, terutama siswa sekolah dasar. Anak-anak memerlukan media pembelajaran yang tidak hanya memberikan informasi, tetapi juga mampu menarik perhatian mereka. Funny hand puppet sebagai alat bantu visual dan verbal dapat menjadi solusi inovatif untuk menyampaikan materi tentang mitigasi bencana. Edukasi mitigasi bencana sejak dini menjadi langkah strategis untuk membangun kesadaran dan kesiapan menghadapi potensi bencana. Pada siswa sekolah dasar, metode penyampaian materi yang interaktif dan menyenangkan diperlukan agar materi lebih mudah dipahami. Salah satu metode yang efektif adalah storytelling dengan menggunakan media funny hand puppet. Tujuan: Untuk mengetahui pengaruh story telling menggunakan funny hand puppet tentang mitigasi bencana banjir  terhadap tingkat pengetahuan siswa sekolah dasar. Metode: Penelitian kuantitatif pre-post-test one group, dilaksanakan pada Mei 2025 di SD Bina Insan Islamic, Palembang. Teknik pengambilan sampel menggunakan total sampling dengan jumlah sampel yang digunakan sebanyak 30 partisipan. Variabel independen dalam penelitian ini adalah story telling funny hand puppet, sedangkan variabel dependen ialah tingkat pengetahuan. Analisis data yang digunakan univariate dalam bentuk distribusi frekuensi dan bivariate menggunakan Wilcoxon test. Hasil: Adanya peningkatan signifikan tingkat pengetahuan siswa setelah intervensi story telling menggunakan funny hand puppet. Nilai median pengetahuan meningkat dari 9.73 menjadi 11.40 dengan p value = 0.000 (p < 0.05). Simpulan: Ada pengaruh yang signifikan sebelum dan sesudah pemberian intervensi tentang mitigasi bencana banjir terhadap tingkat pengetahuan siswa.   Kata Kunci: Edukasi; Hand Puppet; Mitigasi; Pengetahuan; Story Telling Funny.